Assessment of the validity and potential usefulness of the non-linear Saunier model in predicting thermal solar collectors performance - Ang, Koo Soon; Saunier, G.Y.; Exell, Robert H.B., Examination Committee; Walter, Despiegelaere, Ir.; Government of Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1981)
This study is concerned with the assessment of the validity and potential usefulness of the Non-Linear Saunier 's model . After having briefly summarized the equations and formulae of the model, and approximations are made for the effective transmittance absorptance product as well as for the effective environment temperature. In addition, an outline of the computer program which has been developed to compute the significant intrinsic parameters from the experimental data is presented. Tests based on the thermal performance of five computer simulated hypothetical(3) and three commercial(4) solar collectors, show that the Non-Linear Saunier ' s Model described adequately the influences of the fluid temperature, the wind speed of the surrounding , and the surrounding infra-red and the solar radiation fluxes on the collector performance. Furthermore it is shown that the significant intrinsic parameters of t he model can be determined by fitting the performance curve of the model with very few experimental data obtained at the two end conditions (i.e. at T-f close to Ta and stagnation conditions) without affecting the accuracy of the model. Hence a much simplified and less time consuming experimental test procedure for characterizing thermal solar collectors can be proposed .
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Solar collectors